A Modular Design of Continuously Tunable Full Color Plasmonic Pixels with Broken Rotational Symmetry. (5th November 2021) - Feng, Rui; Wang, Hao; Cao, Yongyin; Zhang, Yanxia; Ng, Ray J. H.; Tan, You Sin; Sun, Fangkui; Qiu, Cheng‐Wei; Yang, Joel K. W.; Ding, Weiqiang
Abstract: Color tuning is a fascinating and indispensable property in various applications. Thus far, a variety of reconfigurable approaches have been implemented to achieve color change. However, it is still a challenge to enable continuous color tuning over the entire hue range in a simple, stable, and rapid manner without changes in configuration and material properties. Here, an all‐optical continuously tunable plasmonic pixel scheme is demonstrated via a modular design approach to realize polarization‐controlled full color tuning by breaking the intrinsic symmetry of the unit cell layout. The polarization‐controlled full color tunable plasmonic pixels consist of three different types of color modules corresponding to three subtractive primary colors. Without changing the structural properties or surrounding environment, the structural colors can be continuously and precisely tuned across all hues by illuminating linearly polarized light with different polarization directions. Meanwhile, the plasmonic pixels can be flexibly customized for various color tuning processes through the appropriate choice of component modules and the elaborate design of module layouts. Furthermore, the color tuning is extended to achromatic colors with the utilization of a single module or the introduction of a black module. The proposed plasmonic pixels hold considerable potential to function as next‐generation color pixels integrated with liquid‐crystal polarizers. Abstract : An all‐optical continuously tunable plasmonic pixel scheme is demonstrated via a modular design approach to realize polarization‐controlled full color tuning by breaking the intrinsic symmetry of the unit cell layout. These plasmonic pixels can be flexibly customized for various color tuning processes through the appropriate choice of component modules and the elaborate design of module layouts.